A farmer group model to promote innovation update and market access for cattle and pig value chains in Northwest Vietnam - Nguyen Thi Thinh; Lo Quang Thanh; Atieno, Mary; Bravo, Aura; Burkart, Stefan; Marshall, Karen; Rao, James (International Livestock Research Institute, 2025)
Farmers’ organisations, such as self-help groups, clubs, associations, farmer groups or cooperatives, have been found to positively influence sustainable development of smallholder agriculture by improving information exchange, enhancing skills, and boosting market and service access. Various models of farmer groups are employed by both public and private sectors in low- and middle income countries to enhance the adoption of innovations and smallholder’s value chain integration. However, these models often face sustainability challenges due to heavy reliance on external support instead of internal demand and resources, with little focus on transitioning to self-sustaining management after external backing ends. The CGIAR Sustainable Animal Productivity for Livelihoods, Nutrition, and Gender Inclusion (SAPLING) initiative (2022–2024) aimed to strengthen pig and cattle value chains in northwest Vietnam through context-based co-design and co-testing of a novel social farming approach, ensuring its effectiveness and sustainability beyond the project cycle. The model was tested for eight farmer groups in Mai Son District, Son La Province, with four key steps: (1) identifying core farmer groups that were actively involved in pig and/or cattle production and marketing, and expressed a willingness to take part in the project, (2) improving the operational efficiency of these groups, (3) increasing their visibility within local communities, and (4) influencing policies to ensure their post-project sustainability. Results showed the model’s effectiveness in promoting innovation adoption and connecting farmers to markets. By October 2024, the eight groups expanded to include 692 member households, a significant increase from 127 in 2023, with a composition of 30% women and 70% men. These households implemented at least one technical innovation from SAPLING, such as artificial insemination, feeds and forages, and animal health, benefiting 3,321 farmers. A Livestock Production and Trade Alliance was established, with support from the local government, to enhance the connectivity of these farmer groups with other stakeholders in the regional livestock value chains. The model has received recognition and endorsement from local authorities and has been integrated into Mai Son District’s National Target Program, with recommendations for broader implementation and scaling in Son La Province and the northwest region of Vietnam.